Local Error Analysis and Comparison of the Swept- and Intersection-Based Remapping Methods (Communications in Computational Physics, 2018)
In this paper, the numerical error of two widely used methods for remappingof discrete quantities from one computational mesh to another is investigated. Wecompare the intuitive, but resource intensive method utilizing intersections of computationalcells with the faster and simpler swept-region-based method. Both algorithmsare formally second order accurate, however, they are known to produce slightly differentquantity profiles in practical applications. The second-order estimate of the errorformula is constructed algebraically for both algorithms so that their local accuracy canbe evaluated. This general estimate is then used to assess the dependence of the performanceof both methods on parameters such as the second derivatives of the remappeddistribution, mesh geometry or mesh movement. Due to the complexity of such analysis,it is performed on a set of simplified elementary mesh patterns such as cell cornerexpansion, rotation or shear. On selected numerical tests it is demonstrated that theswept-based method can distort a symmetric quantity distribution more substantiallythan the intersection-based approach when the computational mesh moves in an unsuitabledirection.